The monk - Lewis, M. G. (Matthew Gregory), 1775-1818.; Peck, Louis F. (New York, Grove Press, 1952)
The monk, Ambrosio is abandoned by his parents as an infant. Raised in a monastery, he is a religious fast-tracker taught to disdain sin and hold himself up as a model of purity, untempted by secular pleasure. In Madrid, as the novel begins, he is the young abbot, leader of a monastery. A mesmerizing public speaker, Ambrosio becomes proud and vain, as his popular weekly sermons quickly raise him to the status of an idol. Mischief and misfortunes ensue as Ambrosio's real virtues are put to the test.
NLJCols20082021
Keywords: Monks -- Fiction; Incest -- Fiction; Rape -- Fiction; Incest; Monks; Rape; Madrid (Spain) -- Fiction; Spain -- Madrid; Fiction